Tathwir wasilat fidiu al-rasum al-mutaharika limawad al-istima' fi ta'lim al-lughah al-'arabiyah fi al-saff al-'ashir bil-madrasah al-'aliyah al-jihad Buanjin Luwu al-Shamaliyah - Alfiani Wahid; Kartini; Alfan Putra (Al Ibrah: Journal of Arabic Language Education, 2023)
This research aims to describe the development of an animated video tool for listening materials in teaching Arabic language in the tenth grade at Al-Jihad High School in Buanjin, and to describe the effectiveness of the animated video tool for listening materials in teaching Arabic language in the tenth grade at Al-Jihad High School in Buanjin. This research relies on the ADDIE model, which consists of (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research was conducted at Al-Jihad High School in Northern Buanjin by involving 9 respondents from August to September 2022 to determine the feasibility level of the learning tool. The results of this developmental research are: (1) Animated video products that contain educational materials and animations for students and teachers, attractive presentations, and training questions; (2) The feasibility level of the multimedia learning tool based on audiovisual Arabic language for tenth-grade students was rated by media experts with an overall average of 74% in the "Effective" category, by subject matter experts with an overall average of 90% in the "Very Effective" category, individual testing with an overall average of 80% in the "Effective" category, and tests conducted by students with an overall average of 93% in the "Very Effective" category. Therefore, it can be concluded that the animated video tool for learning audiovisual Arabic language that was developed is highly feasible for use with an overall average of 85%. هذا البحث يهدف إلى وصف تطوير وسيلة فيديو الرسوم المتحركة المواد الاستماع في تعليم اللغة العربية في الصف العاشر بالمدرسة العالية الجهاد بوانجين، و وصف فعالية وسيلة فيديو الرسوم المتحركة المواد الاستماع في تعليم اللغة العربية في الصف العاشر بالمدرسة العالية الجهاد بوانجين. يعتمد هذا البحث على نموذج ADDIE وهي عبارة عن (1) التحليل، (2) التصميم، (3) الطوير، (4) التطبيق، و (5) التقييم. تم إجراء هذا البحث في المدرسة العالية الجهاد بوانجين لووو الشمالية من خلال إشراك 9 المدعى عليه في أغسطس إلى سبتمبر 2022 لتحديد مستوى جدوى وسيلة التعلم. نتائج هذا البحث التنموي هي: (1) منتجات فيديو متحركة تجتوي على مواد تعليمية ورسوم متحركة للطلاب والمعلمين و عروص جذابة وأسئلة تدريب (2) حصل مستوى جدو تعلم الوسيلة المتعددة على أساس اللغة العربية السمعي البصري لطلاب الصف عشر بو اسطة خبراء الإعلام على متوسط إجمالي قدره 74% في فئة "فعال"، من قبل خبراء المواد الذين حصلوا على متوسط إجمالي قدره 90% مع "فعال جدا"،" والاختبار من الفردية على متوسط إجمالي قدره 80 وهي " فعال"، وحصلت الاختبارات التي أجراها الطلاب على متوسط إجمالي قدره 93% في فئة " فعال جدا"، لذلك يمكن استنتاج أن وسيلة الفيديو المتحركة لتعلم اللغة العربية السمعية والبصرية التي تم تطويرها مجدية جدًا للاستخدام على متوسط إجمالي قدره 85%